Long-term operation of a small biogas/diesel dual-fuel engine for on-farm electricity generation - Tippayawong N. (2014)
Biogas from anaerobic digestion of animal manure waste can be used as a renewable energy source for on-farm power generation. In this study, biogas was used in a single-cylinder, direct-injection, compression ignition engine, which has been modified to operate under dual-fuel condition to generate electricity. The primary fuel is biogas, which is ignited by a pilot diesel liquid injection. Long-term engine operation up to 2000 h was carried out. Performance in terms of output power, specific fuel consumption and thermal efficiency was evaluated over a fixed load and a range of engine speeds, and compared against a conventional diesel engine for the first 50 h of operation. Engine components were weighed, inspected visually and given rating for wear, at the start and after 2000 h of operation. Results indicated that short-term performance between conventional diesel and dual-fuel operations was comparable. Biogas/diesel dual-fuel engine was observed to operate successfully with biogas substitution rate at above 90% by mass. Long-term fuel economy was not found to be adversely affected by running time, and the engine was able to maintain 1.45 kW output of electricity throughout the period. Thin layers of carbon deposits were found to build up on the piston, combustion chamber wall, the intake port and exhaust valve stems. Minor surface wear was evident but not significant enough to cause deterioration in engine performance. Overall, the dual-fuel engine appeared to perform well and have great potential for useful on-farm energy utilisation. © 2007 IAgrE.